The neuroprotective effect of BSA-based nanocurcumin against 6-OHDA-induced cell death in SH-SY5Y cells - Roksana Sookhaklari; Bita Geramizadeh; Morteza Abkar; Maryam Moosavi (Mashhad University of Medical Sciences, 2019)
Objective: Parkinson's disease (PD) is regarded as the second most common neurodegenerative disease affecting elderly population. There is a tendency toward finding natural cures to suppress the initiation and progression of this disease. Some epidemiological studies indicated lower incidence of PD in populations that consume curry. Curcumin, as the main ingredient of turmeric, has been supposed to have a protective role against PD progression. However, low bioavailability of curcumin is still a challenge in evaluation of the therapeutic potential of this substance. In this study, we aimed to produce a BSA-based nanocurcumin to assess its effect on 6-hydroxydopamine (6-OHDA)-induced death and Akt signaling disruption in SH-SY5Y cells. Materials and Methods: BSA-based nanocurcumin was produced using desolvation method. Human neuroblastoma cells were treated with OHDA with/without different doses of nanocurcumin and MTT test was used to assess their viability besides observing cells morphological changes. The protective doses of nanocurcumine were chosen according to MTT results and western blot studies were done to assess p-Akt/t-Akt ratio. Results: 6-OHDA exposure led to decreased cell viability, while nanocurcumin at doses of 400 and 500 nM prevented cell death. Moreover, this nanoformulation of curcumin restored p-Akt/t-Akt decrement induced by 6-OHDA. The protective effect of BSA-based nanocurcumin was estimated to be at least 4 time higher than that of natural curcumin according to the MTT results. Conclusion: It seems that BSA-based nanocurcumin can be regarded as a potent substitute for natural curcumin in protecting SH-SY5Y cell as a cellular model of PD.